2014
DOI: 10.1016/j.jvs.2014.08.105
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between kidney disease and endothelial function in peripheral artery disease

Abstract: Objective We have previously shown that peripheral artery disease (PAD) is associated with marked impairment of endothelial function (EF). Given that poor EF is associated with functional status of PAD patients as well as increased morbidity and mortality in patients undergoing vascular procedures, determining factors associated with poor EF in a PAD cohort is important. We hypothesized that decreased kidney function is associated with impaired endothelial function (EF) in patients with PAD. Methods This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Albuminuria leads to a reduction in the endothelium-dependent vascular relaxation response in glomerular endothelial cells [18]. Potential mediators between kidney function and endothelial function included ADMA and TNF-α [19]. Similar results were found by Recio-Mayoral et al [20] and Shukla et al [21] who observed that hemodialysis and CKD stage 4patients had reduced FMD values as compared to controls.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Albuminuria leads to a reduction in the endothelium-dependent vascular relaxation response in glomerular endothelial cells [18]. Potential mediators between kidney function and endothelial function included ADMA and TNF-α [19]. Similar results were found by Recio-Mayoral et al [20] and Shukla et al [21] who observed that hemodialysis and CKD stage 4patients had reduced FMD values as compared to controls.…”
Section: Discussionsupporting
confidence: 70%
“…Similar results were found by Recio-Mayoral et al [20] and Shukla et al [21] who observed that hemodialysis and CKD stage 4patients had reduced FMD values as compared to controls. Chong et al [19] found an inverse relationship between renal function and FMD in symptomatic peripheral arterial disease.…”
Section: Discussionmentioning
confidence: 97%
“…[24][25][26] Although CKD is an important determinant of cardiovascular morbidity and mortality, its role in PAD remains imprecisely defined. [26][27][28][29][30] Of note, in the BASIL trial the presence of ESRD was an exclusion criterion. 5 Patients with CKD and especially ESRD represent unique subgroups with special needs, and the treating physicians should be aware of the negative impact of CKD on the prognosis of CLI.…”
Section: Discussionmentioning
confidence: 99%
“…The most important risk factors for the development of PAD are similar to those for other atherosclerotic vascular diseases which include diabetes, smoking, hypetension, and hyperlipidemia . Impaired endothelial function and increased vascular calcification are other factors that may contribute to the development of PAD and adverse outcomes in ESRD patients . Kidney disease is known to produce a state of oxidative stress and inflammation, both of which are strong depressors of endothelial function.…”
Section: Discussionmentioning
confidence: 99%